Five new anamorphic powdery mildews from India - KAMAL; D.K. AGARWAL, NASIM AHMAD*, AK. SARBHOY (Indian Phytopathology, 2005)
Five new anamorphic powdery mildews viz., Oidium cassiae-Ieschenaultianae, O. cassiae-torae, O. crotalariae, O. heliotropii-strigosum and O. roylae collected on Cassia leschenaultiana L., Cassia torae L., Crotalaria juncea L., Heliotropium strigosum, and Roylea cinerea (D. Don) Baill. respectively, from Northern India bordering mid-Himalayan region are described and illustrated.